Assessment of knowledge, attitude and practice of antenatal mothers on child’s immunization in Raichur district, Karnataka - Ramalingam, Revathi; Ajay, J; Chetty, Sanjeev (Indian Journal of Child Health, 2017)
Objectives: To assess the knowledge, attitude and practice (KAP) of antenatal mothers on child’s immunization and to know the factors affecting the completeness of vaccination and coverage. Design: A questionnaire based cross-sectional study. Setting: Navodaya Hospital, Raichur in the months of June and July 2016. Participants: 200 antenatal inpatients and outpatients mothers. Intervention: A questionnaire comprising 18 questions were administered to the mothers to assess their KAP regarding child’s immunization. Their responses were analyzed using Chi-square test with a value of p<0.05 considered as significant. EPI info version 12 and SPSS 16.0 software were used to analyze the data. Results: Demographic factors of the mother did not have a significant impact on immunization of child. 76.5% of them acquired knowledge regarding through health workers, 60% of the mothers did not know the existence of different types of vaccines, but polio has gained the highest attention of 84% among the diseases. 74% were aware that immunization is free of cost from the government. Responses regarding attitude showed, 96% were willing to get their children vaccinated, 83% felt that the vaccines were harmless, 44% had a fear of side effects due to the vaccines, and 60% of them own an immunization card. Conclusion: The KAP regarding immunization of child in antenatal mothers of Raichur is favorable to the society but fear, lack of awareness and knowledge that prevent the reaching of set targets, can be eliminated by health-care professionals through their timely counseling and interventions in antenatal mothers to achieve completeness and coverage.